Does Extract of Pleurotus sajor-caju affect Liver Enzymes and Histological Integrity? - Nik Norliza, N. H.; Tengku Farah Adilah, T. A.; Siti Hajar, M.; Wan Amir Nizam, W.A.; Wan Rosli, W. I. (Microscopy Society of Singapore, 2014)
Pleurotus sajor-caju (PSC) was believed to have both antihyperlipidemic and hepatoprotective activities. The present study aimed to investigate the effect of PSC on liver enzymes and histological integrity. This study used five groups of rats fed with ghee in the ratio 32g ghee per 68g pellet to induce hypercholesterolemia and one group was fed on cholesterol free basal diet. Rats treated with 100 mg/kg of PSC for a month was found to have an effect on the liver enzymes activities since plasma alkaline phosphatase (ALP) concentration in this group showed a significant reduction (P<0.05) and a higher percentage reduction (66.01%) as compared to 20 mg/kg-PSC and 200 mg/kg- PSC treatment groups. The plasma aspartate aminotransferase (AST) and alanine aminotransferase (ALT) only showed a mild increased by 35.04% and 15.00% respectively in 100 mg/kg-PSC treatment group and there was no significant increased (P>0.05) found in these both AST and ALT concentrations. Atorvastatin treatment also showed reduction in ALP enzymes but no significant reduction (P>0.05) as compared to 100 mg/kg-PSC treatment group. On the other hand, plasma AST and ALT in 20 mg/kg of atorvastatin treatment were increased in percentage by 275.97% and 112.50% respectively indicated the adverse effects of statin in term of elevation of plasma enzymes activities. On the histological part, there was no significant finding in the micrograph study between treatment and hypercholesterolemic (HPC) liver rat. The micrograph of rat liver treated with 100 mg/kg PSC showed smooth and clear surface of hepatocytes compared to HPC group.